AuthorAR : authoring tool for building educational activities based on augmented reality - Moralejo, María Lucrecia
This paper presents an authoring tool for creating educational activities based on Augmented Reality (AR), called AuthorAR. Due to its possibilities to create exploratory and structuring phrases activities, it could be use in special education to favor language acquisition and the development of communication skills. Based on a review of the background for Augmented Reality applications in the area of disabilities, systems can be classified as [5]: In this paper, an introduction is presented, where a detailed background on the use of Augmented Reality for the educational scenario mentioned above is provided, along with some previous works of the authors in the area. Then, AuthorAR is described accompanied by some examples of activities created for special education context. Finally, a brief description of the assessment plan to be implemented is given.